Analisis Relasi Makna Sinonim Bahasa Sasak Dialek Meno-Meni Desa Sakra Kecamatan Sakra - Lalu Purnama Zulkarnaen; Sri Sukarni; Nur Fadilah hidayati (Cordova Journal, 2025)
This study aims to describe the form of synonym meaning relations in the Sasak language of Sakra Village, Sakra District, East Lombok, Meno-MenE dialect. The method used is a descriptive method with a qualitative approach. The data for this study are words, expressions or utterances in the form of synonyms from the Sakra Pusat Village Community, Sakra District, East Lombok. The data source was obtained from members of the Sakra Pusat Village community, Sakra District, East Lombok who live in the village. The sampling technique used in this study was purposive sampling with the selection of informants according to the specified criteria. The techniques for obtaining data are observation techniques, interviews, fishing techniques, recording techniques and note-taking techniques. As for the data validation test, the researcher chose the data source triangulation technique. In data analysis, the researcher read the transcription, re-checked the grouping or categorization of data contained in the word list that had been prepared by the researcher, described the data, and concluded about the synonym and antonym meaning relations. Based on the results of data analysis, it can be concluded that in the Sasak language of the Meno-MenE dialect of Sakra Pusat Village, Sakra District, there are synonyms, namely: 1) synonyms with the same meaning, 2) synonyms with almost the same meaning. In the data, synonyms with the same meaning are divided into several word classes, namely: in the verb, noun, adjective, numeral, prepositional phrase, pronominal, negation classes.